2020
DOI: 10.1093/jncics/pkaa051
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Folate and Folic Acid Concentrations: Associations With Colorectal Cancer Recurrence and Survival

Abstract: Abstract Background Folates, including folic acid, may play a dual role in colorectal cancer development. Folate is suggested to be protective in early carcinogenesis but could accelerate growth of premalignant lesions or micrometastases. Whether circulating concentrations of folate and folic acid, measured around time of diagnosis, are associated with recurrence and survival in colorectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…According to Ting PC, Lee WR [ 18 ] study; patients who take folic acid had a significant improve in CRC survival, that was attributed to its role in inhibiting colorectal cancer cell proliferation and migration. However, a different result was observed in Focus consortium [ 19 ] study as folic acid levels and its derivatives were not associated with neither CRC survival nor CRC recurrence. In 2003, a cohort study found that CRC patients who took both 5FU and folinic acid had less survival rate than those who took 5FU alone [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
“…According to Ting PC, Lee WR [ 18 ] study; patients who take folic acid had a significant improve in CRC survival, that was attributed to its role in inhibiting colorectal cancer cell proliferation and migration. However, a different result was observed in Focus consortium [ 19 ] study as folic acid levels and its derivatives were not associated with neither CRC survival nor CRC recurrence. In 2003, a cohort study found that CRC patients who took both 5FU and folinic acid had less survival rate than those who took 5FU alone [ 20 ].…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, CORSA represents an active and leading player in cooperation, support actions, and consortia. So far, CORSA contributed to multiple international consortia such as Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], COlorectal cancer GENeTics (COGENT) and COnsortium of METabolomics Studies (COMETS) [ 13 ]. Furthermore, CORSA was a partner in two ERANET-TRANSCAN-funded projects: MetaboCCC [ 11 , 12 , 44 , 45 , 46 , 50 , 51 ], and “Biomarkers related to folate-dependent metabolism in colorectal cancer recurrence and survival” (FOCUS) [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…With FOCUS, we study associations between folate and folate-mediated 1-carbon metabolism biomarkers and patient-reported outcomes such as quality of life (17) as well as clinical outcomes among patients aged 18 y and older diagnosed with primary CRC. The FOCUS Consortium has been previously described (11,18 Detailed data on clinical and sociodemographic features, including CRC treatment regimens, disease stage/site, and follow-up were prospectively captured. Comprehensive data on lifestyle features [including BMI (in kg/m 2 ) and smoking history] were also collected when available and harmonized across all study sites.…”
Section: Study Populationmentioning
confidence: 99%
“…Baseline blood samples from CRC patients were processed in identical settings across all study centers as previously described (11,18), and metabolic profiling of biomarkers for all patients in the FOCUS Consortium was performed at BEVITAL AS (www.bevital.no). B6 vitamins and functional markers of vitamin B6 status (23), reflecting the metabolic effects of vitamin B6 serving as an enzyme cofactor, including the following: PLP (nmol/L), pyridoxal (PL) (nmol/L), 4-pyridoxic acid (PA) (nmol/L), 3 -hydroxykynurenine (HK) (nmol/L), kynurenic acid (KA) (nmol/L), 3 -hydroxyanthranilic acid (HAA) (nmol/L), anthranilic acid (AA) (nmol/L), xanthurenic acid (XA) (nmol/L), and creatinine (umol/L) were analyzed by LC-MS. PLP is the biologically active form of vitamin B6, PL is the 4-carboxyaldehyde form of vitamin B6, and PA is the end product of vitamin B6 catabolism.…”
Section: Measurement Of Biomarkers Of Vitamin B6 Statusmentioning
confidence: 99%